AN ANALYSIS OF SELF-REGULATED LEARNING ON MATHEMATICS EDUCATION STUDENT FKIP UNDANA - Damianus D Samo (IKIP Siliwangi and I-MES, 2016)
This research aims to explore the differences among self regulating learning aspect of math education students-FKIP Undana involving three groups of students which are the first level (the first semester), second level (fifth semester) and third level (ninth semesters) students to review the ability of the individual. The samples included 167 students that consist of 60 students of the first level (18 with high ability; 27 with average ability and 15 with low ability), 64 students of the second level (16 with high ability, 30 with average ability and 18 with low ability) and 43 students of the third level (6 with high ability, 24 with average ability and 13 with low ability). This research is a survey research. The data collection is done by distributing questionnaires on self-regulated learning to those three groups. SRL questionnaire consists of 10 aspects, goal setting, motivation, learning difficulties analysis, self-efficacy, election strategies, meta cognition, resource management, performance evaluation, evaluation of the understanding, and self-satisfaction. Two-way ANOVA was utilized in the data analysis of this study. The results of the analysis showed that, the first level group is more excellent in SRL than two other levels. In a review of capabilities, the average comparison of all three groups showed that the average-ability students excel both the high and low-ability students in SRL.